Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To verify that [tex]\( g(x) = \frac{1}{3}x \)[/tex] is the inverse of [tex]\( f(x) = 3x \)[/tex], we need to show that [tex]\( g(f(x)) = x \)[/tex] and [tex]\( f(g(x)) = x \)[/tex].
So let's verify both conditions:
1. Verifying [tex]\( g(f(x)) = x \)[/tex]:
- First, apply [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
- Next, apply [tex]\( g \)[/tex] to this result:
[tex]\[ g(f(x)) = g(3x) = \frac{1}{3}(3x) \][/tex]
- Simplify:
[tex]\[ g(f(x)) = x \][/tex]
This shows that applying [tex]\( g \)[/tex] to [tex]\( f(x) \)[/tex] results in [tex]\( x \)[/tex].
2. Verifying [tex]\( f(g(x)) = x \)[/tex]:
- First, apply [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = \frac{1}{3}x \][/tex]
- Next, apply [tex]\( f \)[/tex] to this result:
[tex]\[ f(g(x)) = f\left(\frac{1}{3}x\right) = 3\left(\frac{1}{3}x\right) \][/tex]
- Simplify:
[tex]\[ f(g(x)) = x \][/tex]
This shows that applying [tex]\( f \)[/tex] to [tex]\( g(x) \)[/tex] also results in [tex]\( x \)[/tex].
Therefore, we have verified that [tex]\( g(x) = \frac{1}{3}x \)[/tex] is indeed the inverse of [tex]\( f(x) = 3x \)[/tex].
Among the provided answer choices, the expression that correctly verifies this relationship is:
[tex]\[ \frac{1}{3}(3x) \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\frac{1}{3}(3x)} \][/tex]
So let's verify both conditions:
1. Verifying [tex]\( g(f(x)) = x \)[/tex]:
- First, apply [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
- Next, apply [tex]\( g \)[/tex] to this result:
[tex]\[ g(f(x)) = g(3x) = \frac{1}{3}(3x) \][/tex]
- Simplify:
[tex]\[ g(f(x)) = x \][/tex]
This shows that applying [tex]\( g \)[/tex] to [tex]\( f(x) \)[/tex] results in [tex]\( x \)[/tex].
2. Verifying [tex]\( f(g(x)) = x \)[/tex]:
- First, apply [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = \frac{1}{3}x \][/tex]
- Next, apply [tex]\( f \)[/tex] to this result:
[tex]\[ f(g(x)) = f\left(\frac{1}{3}x\right) = 3\left(\frac{1}{3}x\right) \][/tex]
- Simplify:
[tex]\[ f(g(x)) = x \][/tex]
This shows that applying [tex]\( f \)[/tex] to [tex]\( g(x) \)[/tex] also results in [tex]\( x \)[/tex].
Therefore, we have verified that [tex]\( g(x) = \frac{1}{3}x \)[/tex] is indeed the inverse of [tex]\( f(x) = 3x \)[/tex].
Among the provided answer choices, the expression that correctly verifies this relationship is:
[tex]\[ \frac{1}{3}(3x) \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\frac{1}{3}(3x)} \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.